STUDY ON MG-AL HYDROTALCITES IN FLAME RETARDANT PAPER PREPARATION - Songlin Wang,; Jianlin Huang,; Fushan Chen (BioResources, 2012)
Mg-Al-CO3 LDH was synthetized, using co-precipitation, and was used in flame-retardant paper as filler. The crystallizations, granularities of Mg-Al LDH, and characters of flame-retardant papers were investigated through XRD, FT-IR, TEM, TG-DTA, and SEM techniques. The results indicated that Mg-Al hydrotalcites were layered hexagonal nanoparticles, with high positive charge density, perfectly crystallized structure, and striking performance in furnish retention improvement. Mg-Al hydrotalcites with high whiteness can improve the whiteness of flame-retardant paper; the whiteness of flame-retardant paper increased by 82.1% while the dosage of LDH was 20wt%, but the Mg-Al hydrotalcites affected the strength index of flame-retardant paper adversely. The flame-retardant papers based on fiber using Mg-Al hydrotalcites as fillers showed excellent inflaming retarding performance. The oxygen index of the flame-retardant paper produced was above 25% at the dosage of 20wt%.